(untitled) (International Journal of Economics Management and Social Science, 2026)
This article examines Lev Vygotsky’s social constructivism theory and its application to collaborative learning in digital technology contexts. Vygotsky’s framework emphasizes that cognitive development occurs through social interaction and cultural tools, with learning situated in zones of proximal development where more knowledgeable others scaffold novice learners. Drawing on contemporary research in educational technology and online learning, this study analyzes how digital platforms enable new forms of collaborative knowledge construction while presenting distinct challenges compared to face-to-face interaction. The COVID-19 pandemic accelerated adoption of digital learning technologies, creating natural experiments in technology-mediated collaborative learning. Analysis of recent empirical studies reveals that digital tools can effectively support Vygotskian principles including peer collaboration, expert scaffolding, and cultural tool mediation, though requiring careful pedagogical design. Findings demonstrate that successful technology-enhanced collaborative learning depends on creating digital environments fostering meaningful interaction, providing appropriate scaffolding structures, and attending to equity issues in technology access. This article contributes to educational sociology by synthesizing Vygotsky’s theoretical framework with contemporary evidence on digital collaborative learning, offering insights for educational practice in increasingly technology-mediated contexts. Keywords: Social constructivism, Vygotsky, collaborative learning, digital technology, zone of proximal development, scaffolding, online education, educational technology